PENGUJIAN FUNGSIONALITAS SISTEM INVENTARIS BARANG BERBASIS WEB PADA SMK NEGERI 7 KABUPATEN TANGERANG DENGAN METODE BLACK BOX TESTING - Frely Cristiadzi Fawaz; Ilhan Fauzan; Romadhon Haris Alfian; Sahidin; Aries Saifudin (Journal of Research and Publication Innovation, 2024)
This research discusses testing a web-based inventory system developed using the Laravel framework at SMKN 7 Tangerang Regency in the Hospitality Teaching Factory, with a focus on the BlackBox testing method. This research aims to test the functionality of the system without paying attention to the internal structure of the code, but from the perspective of the end user. The testing methodology includes functional testing to ensure all features work as expected. The test results show that this system can be relied on for use in the Teaching Factory environment of the Hospitality Department, with good performance. This study provides valuable insights for developers and related parties in improving the implementation of information technology in educational institutions.